Incident hypertension in older women and men with or at risk for HIV infection1. Issue 6 (7th January 2013) - Factor, SH; Lo, Y; Schoenbaum, E; Klein, RS
<x xml:space="preserve">Abstract</x> Objectives Antiretroviral (ARV) therapy has prolonged the life expectancy of HIV‐infected persons, increasing their risk of age‐associated diseases, including atherosclerosis (AS). Decreased risk of AS has been associated with the prevention and control of hypertension (HTN). We conducted a cohort study of perimenopausal women and older men with or at risk of HIV infection to identify risk factors for incident HTN. Methods Standardized interviews, physical examinations, and laboratory examinations were scheduled at 6‐month intervals. Interview data included demographics, medical, family, sexual behaviour and drug use histories, and physical activity. Results There were 330 women and 329 men eligible for inclusion in the study; 27% and 35% of participants developed HTN during a median follow‐up period of 1080 and 1071 days, respectively. In gender‐stratified analysis, adjusting for traditional HTN risk factors (age, race, body mass index, smoking, diabetes, family history of HTN, alcohol dependence, physical activity and high cholesterol), HIV infection was not associated with incident HTN in women [hazard ratio (HR) 1.31; 95% confidence interval (CI) 0.56, 3.06] or men (HR 1.67; 95% CI 0.75, 3.74). Among HIV‐infected women, although exposure to ARVs was not significantly associated with incident HTN (HR 0.72; 95% CI 0.26, 1.99), CD4 T‐cell count was positively associated with incident HTN (HR 1.15 per 100 cells/μL; 95% CI 1.03, 1.28). Among physically active HIV‐infected men, exposure to ARVs was negatively associated with incident HTN (HR 0.15; 95% CI 0.03, 0.78). Conclusions HIV infection was not associated with incident HTN in older men or women. This study provides additional evidence supporting a causal relationship between immune function and incident HTN, which warrants further study.